2010
DOI: 10.1103/physrevb.81.054427
|View full text |Cite
|
Sign up to set email alerts
|

Role ofA-site cations in the metal-insulator transition inPr0.5Ca0.5CoO

Abstract: Remarkable structural changes take place during the metal to insulator first-order transition in Pr 0.50 Ca 0.50 CoO 3 : a contraction of the unit-cell volume, the bending of the Co-O-Co bond angle, and a decrease in ͑Pr,Ca͒-O bond distance. However, the Co-O bond length and the volume of the CoO 6 octahedra remain almost unaltered during the transition. In view of these data and the absence of transition in ͑Nd 2/3 La 1/3 ͒ 0.5 Ca 0.5 CoO 3 , we review the current spin-state transition picture, emphasizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 40 publications
5
60
0
Order By: Relevance
“…This scenario was originally suggested in order to account for anomalous shortening of some Pr-O bondlengths, whereas the expected shrink of the CoO 6 octahedra due to the stabilization of lower spin states of Co has not been observed [6]. The existence of Pr→CoO 3 electron transfer was supported later theoretically by GGA+U electronic structure calculations exploiting the temperature dependence of the structural experimental data for Pr 0.5 Ca 0.5 CoO 3 [7], and experimentally, in particular by observation of Schottky peak in the low temperature specific heat, related to Zeeman splitting of the ground doublet of Kramers ions Pr 4+ [8].…”
Section: Jhejtmanek Et Al Phase Transitionspage 2 Of 19mentioning
confidence: 99%
“…This scenario was originally suggested in order to account for anomalous shortening of some Pr-O bondlengths, whereas the expected shrink of the CoO 6 octahedra due to the stabilization of lower spin states of Co has not been observed [6]. The existence of Pr→CoO 3 electron transfer was supported later theoretically by GGA+U electronic structure calculations exploiting the temperature dependence of the structural experimental data for Pr 0.5 Ca 0.5 CoO 3 [7], and experimentally, in particular by observation of Schottky peak in the low temperature specific heat, related to Zeeman splitting of the ground doublet of Kramers ions Pr 4+ [8].…”
Section: Jhejtmanek Et Al Phase Transitionspage 2 Of 19mentioning
confidence: 99%
“…[3][4][5] Based on the electronic structure calculations and detailed analysis of the structural, electrical, magnetic, and specific heat data, it has been found that the transition is accompanied by a significant charge transfer between cobalt and praseodymium ions. In particular for the system (Pr 1Ày Y y ) 0.7 Ca 0.3 CoO 3 , about onethird of the Pr 3þ ions changes their valency to Pe 4þ during the SST on decreasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of the 4-fold tetragonal axis brings on degeneration and two equivalent magnetic easy-axes, which are associated to the two conjugated magnetic domains with spin orientations [110] and [1][2][3][4][5][6][7][8][9][10]. Therefore, the loss of magnetization (negative step) under low fields (H< H cr ) is produced by the presence of conjugated [110] and [1][2][3][4][5][6][7][8][9][10] ferromagnetic domains after the Imma → I4/mcm transition. A schematic view of magnetic ordering and magnetic domains above and below T S1 is shown in Figure 9.…”
Section: Discussionmentioning
confidence: 99%